One-step chemical synthesis of MgCNi3 nanoparticles embedded in carbon nanosheets utilizing waste polyethylene as carbon source. (24th January 2020) - Wang, Liangbiao; Dai, Weicheng; Yang, Tinghai; Zhang, Kailong; He, Wanyu; Kong, Qianyu; Zhang, Junhao; Wang, Xian; Mei, Tao; Hu, Yuhua; Shen, Hanqi; Qian, Yitai
Abstract: MgCNi3 nanoparticles embedded in carbon nanosheets have been successfully synthesized from waste polyethylene (PE) by one-step chemical reaction at a relatively low temperature of 800 °C. X-ray diffraction pattern indicates that the obtained sample is anti-perovskite structured MgCNi3 . Transmission electron microscopy image shows that MgCNi3 nanoparticles are embedded in the carbon nanosheets. Magnetization measurement shows that the obtained sample has a superconducting transition at 6.8 K. This method is not only to develop an effective method to synthesize MgCNi3 superconductor under mild conditions but also to provide a novel technique to convert waste polyethylene to valuable carbide materials.